Gut Microbiome-Mediated Alteration of Immunity, Inflammation, and Metabolism Involved in the Regulation of Non-alcoholic Fatty Liver Disease - He, Li-Hong; Yao, Dun-Han; Wang, Ling-Yun; Zhang, Lei; Bai, Xue-Li (Frontiers in Microbiology, 2021)
The term “gastrointestinal microbiome (GM)” refers to the approximately 100 trillion microbial cells that inhabit the host’s gastrointestinal tract. There is increasing evidence of the involvement of the GM in non-alcoholic fatty liver disease (NAFLD). Strategies targeting the GM for the diagnosis and treatment of NAFLD have been proposed. A more comprehensive and in-depth understanding of the host-microbe interaction is needed to promote more clinical transformation and the development of precision and personalized medicine to reduce the severe global disease burden of NAFLD. This review evaluates this interaction critically, mainly considering the intricate metabolic and immune/inflammatory homeostasis regulation, revealing roles for the GM in NAFLD by examining advances in potential mechanisms, diagnostics, and modulation strategies.